Interfacial Tension Modulation of Liquid Metal via Electrochemical Oxidation. (13th May 2021) - Song, Minyung; Daniels, Karen E.; Kiani, Abolfazl; Rashid‐Nadimi, Sahar; Dickey, Michael D.
Abstract : Herein, this progress report summarizes recent studies of electrochemical oxidation to modulate the interfacial tension of gallium‐based alloys. These liquid alloys have the largest interfacial tension of any liquid at room temperature. The ability to modulate the tension offers the possibility to create forces that change the shape and position of small volumes of liquid metal. It has been known since the late 1800s that electrocapillarity—the use of potential to modulate the electric double layer on the surface of metals in electrolyte—lowers the interfacial tension of liquid metals. This phenomenon, however, can only achieve modest changes in interfacial tension since it is limited to potentials that avoid Faradaic reactions. A recent discovery suggests reactions driven by the electrochemical oxidation of gallium alloys cause the interfacial tension to decrease from ≈500 mN m −1 at 0 V to ≈0 mN m −1 at less than 1 V. This change in interfacial tension is reversible, controllable, and goes well‐beyond what is possible via conventional electrocapillarity or surfactants. This report aims to introduce beginners to this field and address misconceptions. The report discusses applications that utilize modulations in interfacial tension of liquid metal and concludes with remaining opportunities and challenges needing further investigation. Abstract : Herein, recent studies of the use of electrochemical oxidation to modulate the interfacial tension of gallium‐based alloys are summarized, offering the possibility of changing the shape and position of small volumes of liquid metal. These techniques can drop the interfacial tension to near zero, while also being reversible, enabling a variety of applications.